Ferritinophagy: a possible new iron-related metabolic target in canine osteoblastic osteosarcoma - Power, Karen; Leandri, Rebecca; Federico, Giorgia; De Vico, Gionata; Leonardi, Leonardo (Frontiers in Veterinary Science, 2025)
Canine osteosarcomas (COS) are the most common bone tumors in dogs, characterized by high metastatic rates, poor prognosis, and poor responsiveness to routine therapies, which highlights the need for new treatment targets. In this context, the metabolism of neoplastic cells represents an increasingly studied element, as cancer cells depend on particular metabolic pathways that are also elements of vulnerability. Among these, tumor cells (TCs) show higher iron requirements to sustain proliferation (so-called iron addiction), which are achieved by increasing iron uptake and/or by activating ferritinophagy, a process mediated by the Nuclear receptor Co-Activator 4 (NCOA4) leading to iron mobilization from ferritin (Ft) deposits. Previous studies have shown that COS cells overexpress Transferrin Receptor 1 (TfR1) to increase iron uptake. In this study we evaluated the immunohistochemical expression of ferritinophagy-related proteins, namely Ferritin Heavy chain (FTH1) and NCOA4, and proliferating cell nuclear antigen (PCNA) in canine normal bone and canine osteoblastic osteosarcoma (COOS) samples. Normal samples revealed negative/weak immunoreactivity for FTH1, NCOA4 and PCNA in <10% of osteocytes. In COOS samples the majority of neoplastic cells showed immunoreactivity to FTH1, NCOA4 and PCNA. Our data suggest that the activation of ferritinophagy by COOS cells responds to the need for feed their “iron addiction.” These data, though preliminary, further suggest that targeting iron metabolism represents a new potential strategy worthy of further study to be transferred into clinical practice.